SYSTEMATIC LITERATURE REVIEW: PENYEBAB KECURANGAN - Marita Sekar Febriandani; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2022)
This study aims to identify patterns from previous study that have been published and considered to have the highest impact and references that are considered the most influential. This study focuses on previous research on the topic of fraud. Finally, this study will identify the causes of fraud from the perspective of the fraud triangle theory and its development.The Systematic Literature Review (SLR) method is used to analyze various articles that have been published in academic journals indexed in SCImago Journal Rank (SJR) at the level of first quartile (Q1) and second quartile (Q2). The articles used are articles published in the range of 2012 to 2021 and filtered using selected keywords. This study reviews articles that use the fraud triangle theory as well as articles outside the fraud triangle theory, but still within the scope of discussion related to fraud.The result of the analysis that has been carried out finds that most of studies use the fraud triangle theory as a conceptual framework. The result of the analysis also finds that all the elements in the fraud triangle theory affect fraud, but the level of influence of each element is different. This study explains that opportunity is the element with the greatest level of influence, while rationalization has the smallest level of influence. Moreover, most of research focuses on fraud detection rather than fraud prevention.The findings of this study are expected to provide benefits and a substantial impact on financial fraud and are expected to increase knowledge, also enrich literature related to financial fraud.